INOVASI PEMBELAJARAN SEJARAH KEBUDAYAAN ISLAM DALAM MENINGKATKAN MINAT BELAJAR SISWA DI MADRASAH TSANAWIYAH NEGERI 1 PROBOLINGGO - Wada'ah, Mamluk Nurul; Tohet, Moh. (Universitas Islam Madura, 2024)
SKI learning using the mnemonic learning method and audiovisual media provides new experiences for the success of education in Madrasahs, based on the results of observations conducted by researchers at Madrasah Tsanawiyah Negeri 1 Probolinggo, it shows researchers that they apply interesting learning technology in learning the history of Islamic culture, thus, the feeling Being bored and not enthusiastic about learning becomes positive energy for students to be enthusiastic about returning to learning. This is the reason for researchers to research and explore this phenomenon by carrying out research activities. The focus of this research is the implementation of innovative mnemonic learning methods and audiovisual media in SKI learning. Thus, the research aims to explore innovative mnemonic learning methods and the use of audiovisual media in SKI learning. The research method used is qualitative with a phenomenological type, interview activities, observation and documentation data analysis are the data collection methods used by researchers. The results of the research show that using these methods and media has succeeded in increasing students' interest in learning, meaning that the application of mnemonic learning methods and audiovisual media creates interesting, dynamic and interactive learning, which makes students more enthusiastic and enthusiastic in participating in SKI learning, of course with full support. from teachers and students is the key to the success of this innovation. Meanwhile, the implications of this research include: 1) Increasing interest in learning, 2) Developing learning methods, 3) Enriching the curriculum, 4) Developing learning materials, 5) Strengthening Islamic identity.